Intra-corporeal robotic renal auto-transplantation - Lee, Jason Y.; Alzahrani, Tarek; Ordon, Michael (Canadian Urological Association Journal, 2015)
Renal auto-transplantation (RATx) has been shown to be a suitable option for managing patients with long upper ureteric or pan-ureteric strictures. The current gold standard approach to RATx is a laparoscopic nephrectomy followed by open auto-transplantation. The advent of robotic-assisted laparoscopic surgery has allowed for the application of minimally-invasive techniques to ever-more complex surgical procedures. We present the case of a 38-year old patient referred to our institution for management of a failed laparoscopic pyeloplasty resulting in a completely obstructed ureter. After complete evaluation, RATx was determined to be a suitable management option. Completely intracorporeal right RATx was performed robotically with intraperitoneal cold perfusion. Total OR time was 6.5 hours with total ischemia time of only 79 minutes (4 mins warm ischemia, 48mins cold ischemia, 27mins re-warming time); comparable to the gold standard approach for RATx. To our knowledge, this is the first reported case of a completely intracorporeal robotic renal auto-transplantation in Canada.